ETHNIC IMAGES AND NATIONAL STEREOTYPES IN THE FANTASY-NOVEL GONITWA BY NICKY RAKITINA AND THE ACTION-PACKED NOVEL GOOD ANGEL OF DEATH BY ANDREY KURKOV - Kowalow, Siergiej (Porównania, 2018)
On the example of the fantasy-novel Gonitva written by a young Belarusian author Nicky Rakitina and action-packed novel Good Angel of Death by Andrey Kurkov, the article presents an analysis of the way ethnic images and stereotypes function in the Russian-language literature of Belarus and Ukraine. Works chosen for the analysis belong to the different national literatures and different genres, but clearly indicate the prospects of how writers can turn their views on the national traditions and play with national codes and images.